2008
DOI: 10.1111/j.1442-2042.2008.02053.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for radiation‐induced hemorrhagic cystitis

Abstract: Hyperbaric oxygen (HBO) therapy has recently emerged as a potential primary option for the management of hemorrhagic cystitis. We review our experience treating hemorrhagic cystitis with HBO. Between January 2001 and May 2007, eight patients with radiation-induced hemorrhagic cystitis underwent HBO therapy. There were five men and three women with a mean age of 64.3 years (47-73). Radiation was given for local disease, and the mean dosage delivered was 56.6 Gy (42-70). The mean duration between the onset of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 9 publications
2
48
2
2
Order By: Relevance
“…Moreover, some of them may have serious systematic side effects or may exacerbate bladder fibrosis which was initiated by radiation treatment, leading to a small-capacity bladder (1,(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). A recent Cochrane Database systematic literature review on non-surgical interventions for late radiation cystitis in patients who have received radical radiotherapy to the pelvis concluded that in the absence of randomized controlled studies it is impossible to set definitive rules for treatment (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some of them may have serious systematic side effects or may exacerbate bladder fibrosis which was initiated by radiation treatment, leading to a small-capacity bladder (1,(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). A recent Cochrane Database systematic literature review on non-surgical interventions for late radiation cystitis in patients who have received radical radiotherapy to the pelvis concluded that in the absence of randomized controlled studies it is impossible to set definitive rules for treatment (21).…”
Section: Discussionmentioning
confidence: 99%
“…All studies published on HBO therapy for radiation cystitis are not randomized or controlled. The majority constitutes retrospective reviews and case series (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), with only one study being prospective in nature (14). In all these studies HBO was used as a secondary treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high levels of oxygen deliverable under HBO exposure make this approach attractive. Several studies in experimental animal tumors have shown that HBO reduces the radioresistance of certain types of tumors [6][7][8][9] and enhances the anticancer activity of doxorubicin and other alkylating agents. 10,11 Clinical trials have been initiated to study the effect of HBO inhalation on the radiotherapy for many types of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators have studied HBOT in this setting. 47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64 An advantage of HBOT in these patients is the absence of the adverse effects on bladder structure or function that may be seen with other therapies, such as formalin or silver nitrate instillations, while avoiding the need for surgery. HBOT is also very well tolerated, with few adverse effects-the most common being pressure-related in the form of ear and sinus barotrauma.…”
Section: Hyperbaric Oxygen Therapymentioning
confidence: 99%